2018
DOI: 10.1021/acsanm.7b00403
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Electronic Structure of an Aluminum Phosphide Nanotube through Configuration of the Lattice Geometry

Abstract: The core lattice geometry of an aluminum phosphide (AlP) nanotube is altered from a hexagonal lattice to an octagonal lattice, and its effects on the electronic structure are investigated using first-principles calculations. The binding energy of the octagonal AlP nanotube is calculated to be −0.15 eV/atom, which denotes an exothermic reaction and results in the octagonal AlP nanotube being thermodynamically stable. Al and P atoms possess an average of 11.07 and 16.86 electrons, respectively, suggesting ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Optoelectronics appears to be one of the most vibrant areas in which quantum size effects have been leveraged to achieve unique properties in functional materials including quantum dots, 8,9 chalcogenides, 10−14 perovskites, 15,16 nanowires, 17 black phosphorus, 18 and nanotubes. 19 For instance, the highest photoluminescence quantum yield for metal-doped carbon dots was obtained for Mn, opening up the possibility to develop an ultrasensitive Hg 2+ detector. 9 In a perovskitefocused study, 16 it was reported that the photoluminescence emission profile of MgTiO 3 /LaNiO 3 with dual-color emission maxima centered at 454 and 754 nm is quite distinct from the profiles of its individual constituents with a maximum at 724 nm for MgTiO 3 and insignificant photoluminescence emission for LaNiO 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Optoelectronics appears to be one of the most vibrant areas in which quantum size effects have been leveraged to achieve unique properties in functional materials including quantum dots, 8,9 chalcogenides, 10−14 perovskites, 15,16 nanowires, 17 black phosphorus, 18 and nanotubes. 19 For instance, the highest photoluminescence quantum yield for metal-doped carbon dots was obtained for Mn, opening up the possibility to develop an ultrasensitive Hg 2+ detector. 9 In a perovskitefocused study, 16 it was reported that the photoluminescence emission profile of MgTiO 3 /LaNiO 3 with dual-color emission maxima centered at 454 and 754 nm is quite distinct from the profiles of its individual constituents with a maximum at 724 nm for MgTiO 3 and insignificant photoluminescence emission for LaNiO 3 .…”
mentioning
confidence: 99%
“…Optoelectronics appears to be one of the most vibrant areas in which quantum size effects have been leveraged to achieve unique properties in functional materials including quantum dots, , chalcogenides, perovskites, , nanowires, black phosphorus, and nanotubes . For instance, the highest photoluminescence quantum yield for metal-doped carbon dots was obtained for Mn, opening up the possibility to develop an ultrasensitive Hg 2+ detector .…”
mentioning
confidence: 99%